2009
DOI: 10.1002/pon.1646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylphenidate on fatigue in women with recurrent gynecologic cancer

Abstract: This study provides support for the use of a psychostimulant to treat fatigue in women who have recurrent gynecologic cancer. It is particularly relevant for these patients with incurable disease who are facing the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…Depression in cancer patients may also come with tiredness. In regard to treatment of cancer-related fatigue, methylphenidate has long been studied to be very effective, despite its side effects [9,53]. Modafinil was also well-tolerated and effective against fatigue in cancer patients when self-administrated for four weeks [10].…”
Section: Application For the Countermeasure Of Fatiguementioning
confidence: 99%
“…Depression in cancer patients may also come with tiredness. In regard to treatment of cancer-related fatigue, methylphenidate has long been studied to be very effective, despite its side effects [9,53]. Modafinil was also well-tolerated and effective against fatigue in cancer patients when self-administrated for four weeks [10].…”
Section: Application For the Countermeasure Of Fatiguementioning
confidence: 99%
“…Most drugs were not compared with placebo or did not show significant benefit compared with placebo (Fig. 3) [7,8,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118]. One drug, methylphenidate, showed promising results [111][112][113]119], but in the latest and largest trials, no improvement of fatigue by this treatment was found compared with placebo [114,120,121].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Details and results of this search can be found in supplemental online Appendix 2. Drugs that were studied for their effect on CRF were bupropion [103] [110], methylphenidate [15,[111][112][113][114][115]120], modafinil [2,116], paroxetine [7,8], and thyrotropin-releasing hormone [117]. Most drugs were not compared with placebo or did not show significant benefit compared with placebo (Fig.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Además dentro de los EC con pacientes oncológicos, la mayoría están referidos a diferentes tipos de tumor y con diferentes tratamientos, o en diferentes estadios 4,15,16,21 , donde se encuentra mayor alivio del dolor con metilfenidato en estadios más avanzados o mayor fatiga basal), motivos que puede limitar la interpretación de resultados comparables sobre el beneficio del metilfenidato sobre placebo de los EC estudiados.…”
Section: Tabla 2 Cuadro Resumen De Efectos Secundariosunclassified